Handbook of fillers - Wypych, George (ChemTec Publishing, 2021)
"This handbook gives a direct comparison of general-purpose fillers (micron-size fillers) and nanofillers. Over 5,000 research papers, mostly published from 1994 to 2020 (full review of the most recent papers in this edition), technical data from over 200 filler and equipment manufacturing companies, and current patent literature were reviewed for this comprehensive handbook. The book is designed to be a single source of information for an experienced practitioner as well as a reference text for students and those new to the fields where fillers are used. The previous editions, used by a very large number of readers, do not contain essential developments of extensive research on fillers in the last ten years, especially related to nanofillers, graphene, and other novelty products."--